Analysis of Final PPH Calculations Article 4 Paragraph 2 on Interest Tax on Deposits and Savings at PT. BPR Kartika Matuari Tomohon - Tinggogoy, Vanecia Villea; Sumual, Frida Magda; Evinita, Lenny (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
The purpose of this study is to study the calculation of final income tax for interest tax deposits and savings, which are listed in article 4 para. 2 of the Income Tax Act. BPR Kartika Matuari Tomohon is the subject of this research. Interest tax and accounting calculations are governed by tax regulations and accountancy standards. These calculations must be communicated to all parties involved so that they can be applied effectively and efficiently to avoid losses to consumers and States. Last PPH for Deposit and Savings Flower Tax, Article 4 Paragraph 2, is collected, calculated, and assessed using descriptive methods. In accordance with the Decision of the Minister of Finance No.212/PMK.03/2018 on the reduction of income tax on interest deposits and savings, BPR Kartika Matuari has complied with the applicable tax rules. for a 20% tax rate established in accordance with applicable legal regulations, with the tax calculation formula used to multiply the tax rate by interest charges.